ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INOVASI PURSED LIP BREATHING DAN NUMBER COUNTING PADA PASIEN DENGAN HIPERTENSI URGENSI DI IGD - Sonia Danti, (2023)
Hypertension is a problem that is often overlooked, even though it can occur in around one-third of referred patients and even up to half of those who are difficult to treat. There are two types of hypertension crises, namely urgency hypertension and emergency hypertension, in which urgency hypertension occurs when there is no end organ damage. To address this issue, an innovative intervention using Pursed Lip Breathing and Number Counting was conducted to analyze its effectiveness in reducing blood pressure and pulse rate in patients with urgency hypertension in the emergency department. After three interventions, there was a significant change in systolic and diastolic blood pressure by 20 mmHg. The analysis results showed that Pursed Lip Breathing and Number Counting therapy provided significant changes in blood pressure and pulse rate for patients with urgency hypertension. Keyword: Blood Pressure, Number Counting, Pursed Lip Breathing, Urgency Hypertension